Incidence of oxygen desaturation with intravenous ketamine and the effects of the basic airway management maneuvers on it - Lamgade, Amit; Joshi, A; Kharel, S; McArthur, L (Journal of General Practice and Emergency Medicine of Nepal, 2010)
Introduction: This study was conducted to evaluate and compare the incidence of oxygen desaturation during intravenous ketamine for short surgical procedure and the effects of basic airway management maneuvers during desaturation.Methods: A Population based comparative study was done at two different hospitals situated in hilly regions of Nepal. Children aged between 3 months and 14 years were observed for their oxygen saturation with the help of Pulse Oxymeter during intravenous ketamine anesthesia for short surgical procedures lasting less than 15 minutes.Results: Seventy nine patients from United Mission Hospital (UMN), Tansen and 66 patients from Okhaldhunga Community Hospital (OCH), Okhadhunga were enrolled; the incidence of desaturation was 8(10%) and 11(16.1%) in Tansen and Okhaldhunga respectively. 7(87.5%) and 8(72.7%) of the patients with desaturation from UMH and OCH respectively, were improved to >90% with chin lift only and rest needed jaw thrust.Conclusion: The incidence of oxygen desaturation is common within first few minutes of ketamine administration. Basic airway measures like chin lift and jaw thrust is enough to improve oxygen saturation.